STUDY OF THE EFFECT OF PROFESSIONAL SATISFACTION OF TEACHERS WORKING AT COLLEGE LEVEL ON THEIR WORK STYLE - Singhal, Neetu; Yadav, Garima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The objective of the present research work is to study the relationship between professional satisfaction and work style of teachers of government and private colleges. In this research, 300 teachers working in various government and private colleges of Jaipur district were selected as sample. Simple random sampling method was used for selection. Two main instruments were used for data collection—Teacher Professional Satisfaction Scale created by Dr. Pramod Kumar and Dr. D.N. Mootha and Teacher Work Style Scale created by the researcher. Correlation coefficient was used for analysis of the collected data. It was clear from the research results that no significant effect was reflected between the professional satisfaction and work style of teachers of government and private colleges. Similarly, no significant difference was found in professional satisfaction and work style between teachers (both government and private) of urban and rural areas. This study concluded that the work style of teachers is based on relatively independent and individual tendencies, on which the direct effect of professional satisfaction was found to be less. This research can prove helpful in understanding the multidimensional nature of teacher work style in higher education institutions and in making education policies and teacher training programs more effective in future.